2006
DOI: 10.2341/05-41
|View full text |Cite
|
Sign up to set email alerts
|

Curing Capability of Halogen and LED Light Curing Units in Deep Class II Cavities in Extracted Human Molars

Abstract: SUMMARYClass II cavities were prepared in extracted lower molars filled and cured in three 2-mm increments using a metal matrix. Three composites (Spectrum TPH A4, Ceram X mono M7 and Tetric Ceram A4) were cured with both the SmartLite PS LED LCU and the Spectrum 800 continuous cure halogen LCU using curing cycles of 10, 20 and 40 seconds. Each increment was cured before adding the next. After a sevenday incubation period, the composite specimens were removed from the teeth, embedded in selfcuring resin and gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 15 publications
1
16
0
1
Order By: Relevance
“…As observed by Hasler and others, 14 the microhardness values of all composites were lower close to the matrix. The setup in this study might account for this observation.…”
Section: Discussionsupporting
confidence: 60%
See 3 more Smart Citations
“…As observed by Hasler and others, 14 the microhardness values of all composites were lower close to the matrix. The setup in this study might account for this observation.…”
Section: Discussionsupporting
confidence: 60%
“…As a result, the microhardness numbers remained consistent throughout all depths. According to Hasler and others, 14 a cumulative curing effect can not be taken into consideration in this context. They concluded that it can not be assumed that curing further increments has an effect on the degree of polymerization of underlying layers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, LED systems are often considered similar or comparatively better than QTH system in terms of the degree of polymerization (Hasler et al, 2006), polymerization shrinkage (Uhl et al, 2005), microleakage (Attar and Korkmaz, 2007), wear rate (Ramp et al, 2006), flexural properties (Keogh et al, 2004) and hardness (de Araújo et al, 2008).…”
Section: Introductionmentioning
confidence: 99%